GERAKAN LITERASI SEKOLAH BERBASIS PEMBELAJARAN MULTILITERASI SEBUAH PARADIGMA PENDIDIKAN ABAD KE- 21 - Nopilda, Lisa; Kristiawan, Muhammad (Graduate Program Magister Manajemen Pendidikan, 2018)
The study aimed at obtaining information about the implementation of Literacy School Movement Based Learning Multiliteration (SLM) (Educational Paradigm of 21st Century). This research used qualitative. Data were collected through interview, observation and documentation. The subjects of this study were students and teachers from SMK Negeri 1 Suak Tapeh and the results showed that (1) implementation of School Literacy Movement (GLS) through multiliteration to read, write and speak has entered development and learning which is a progress from habituation that has been done since 2016; (2) in the development and the learning phase, the students were able to make simple papers such as fairy tales, inspirational stories, scientific papers and appropriate technology which displayed on major events such provincial-level student expo and competition; (3) GLS has enhanced the culture of literacy and fostered the character of students to be creative and innovative.